HIJRAH, BETWEEN SOCIOLOGICAL AND THEOLOGICAL PHENOMENON - Firmansyah Firmansyah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2021)
This study examines the Hijrah group in Indonesia as a social and theological movement. Except to be a role model, Hijrah is also interpreted as an effort to get closer to Allah. Today, the understanding of the Hijrah values seems to have shifted and formed a polarization of ignorance in religion with the exclusivity of the group's reason. Hijrah principally is not just a matter of strengthening the religious values symbolically, but also the mission of building an open mind on social and religious plurality. This study uses a literary method and phenomenological descriptive and the socio-theological reason approach of Muhammed Arkoun. The results show that a reason can be formed by a structural systematization model of a group. Hijrah is seen as shifting religious labeling, only existing in the crowd that eventually creates a logical deadlock and forms a new social class. As a result, it is clear that the Hijrah group does not offer individual independence but gives birth to a generation with exclusive minded.